2011
DOI: 10.1186/1758-5996-3-36
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Novel Non-Invasive technology based EZSCAN system for the diagnosis of diabetes mellitus in Chinese

Abstract: BackgroundA new simple technique based on iontophoresis technology (EZSCAN, Impeto Medical, Paris, France) has recently been developed for the screening of diabetes. In the present study, we investigated the accuracy of this system for the diagnosis of diabetes mellitus in Chinese.MethodsWe performed the EZSCAN test in diabetic and non-diabetic subjects. EZSCAN measures electrochemical conductance (EC) at forehead, hands and feet, and derives a diabetes index with a value ranging from 0 to 100. Diabetes mellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 15 publications
1
36
0
1
Order By: Relevance
“…Therefore, it is necessary to monitor disease spectrum changes, and prevent and detect diabetes in the early stage. The results of this study revealed that blood uric acid levels in subjects in the high-risk group were higher than that in the low-risk group and normal group, which was consistent with previous research results [10,16]. From the results of the study, we can observe that even in a high-risk population, the pilots' BMI and blood uric acid values were lower than in the general population.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, it is necessary to monitor disease spectrum changes, and prevent and detect diabetes in the early stage. The results of this study revealed that blood uric acid levels in subjects in the high-risk group were higher than that in the low-risk group and normal group, which was consistent with previous research results [10,16]. From the results of the study, we can observe that even in a high-risk population, the pilots' BMI and blood uric acid values were lower than in the general population.…”
Section: Discussionsupporting
confidence: 81%
“…Ramachandran et al [5] performed EZSCAN and glucose test on 212 subjects and found that when the EZSCAN cut-off point was 50%, the diagnostic sensitivity and specificity of diabetes were 75% and 54%, respectively, and sensitivity was higher than in fasting plasma glucose (FPG, 29%). Sheng et al [10] performed EZSCAN tests on 195 subjects. They also found that conductivity in the diabetic group was significantly lower than in the non-diabetic group.…”
Section: Discussionmentioning
confidence: 99%
“…15 Strengths of our study include good measurement properties for the instrumentation used. [8][9][10][11][12]17,19,21,22 We also allowed for a thermal wash-out period 15 between testing and randomized the insole testing sequence. We assessed for gait and balance changes under single and dual task conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In verschiedenen klinischen Studien war eine gute Korrelation der EZSCAN™-Risikostratifizierung mit Glukose-, Insulin-und Proinsulinwerten, die mit einem oGTT gemessen werden, nachweisbar [38,41]. Außerdem ergaben sich unterschiedliche Scanverläufe bei Patienten, die hyperglykämisch und insulinresistent waren, sich aber durch den Grad des β-Zell-Versagens voneinander unterschieden.…”
Section: -H-glukosemessungunclassified